Seattle, the Pacific Basin, and the Sources of Regional Modernism. Issue 3 (1st September 2016) - Ochsner, Jeffrey Karl
Abstract: The emergence of mid-twentieth-century architecture that was both modern and regional in Seattle and nearby areas of Washington State presents a singular case study demonstrating an array of influences from Asia and Latin America as well as the Pacific Coast of the United States. This network of influences is evidence of the "complexity of a dissemination" that gained momentum in the 1930s as the modern movement began to spread globally, as identified by historian William J. R. Curtis. Although awareness of distant sources primarily influenced design vocabularies from the 1930s to the 1950s in the Pacific Northwest, by the early 1960s, as Seattle architects and landscape architects began to travel to Japan, they developed a much deeper understanding from a broader collection of sites, and this, in turn, shaped surprisingly varied local responses from Rich Haag's ideas of "non-striving" design to Victor Steinbrueck's increasing interest in Pike Place Market. Untangling the array of Pacific Basin influences that helped shape mid-twentieth-century design in Seattle provides one demonstration of the validity of considering the Pacific as an interdependent region. Thus, Seattle offers a foundational case study towards the future project of writing an encompassing account of the interconnected architectural history of the Pacific Basin.